DISPENSASI KAWIN DI DESA KARANGJATI KECAMATAN SAMPANG KABUPATEN CILACAP (Universitas Wijayakusuma Purwokerto, 2024)
The aim of this Community Service is to assist the government in socializing the law and increasing public knowledge of the law, especially regarding the Marriage Dispensation in Karangjati Village, Cilacap District. In carrying out Community Service activities which raise the topic